Determinants of Risk for Type 2 Diabetes Mellitus Among the Community at The Birobuli Community Health Center - Rau, Muh. Jusman; Nurjannah, Nurjannah; Syahadat, Dilla Srikandi; Hasanah, Hasanah (Media Publikasi Cendekia Indonesia, 2024)
To identify the determinants of risk for type 2 diabetes mellitus among the community at the Birobuli Community Health Center. Type of quantitative research with a case-control approach at a confidence level of 95%. The sample size was taken using the Slovin formula with a result of 76 people and a 1:1 ratio and using gender matching with a total sample of 152 people. Sampling was done using the purposive sampling technique. The data source used secondary data in the form of medical records and primary data in the form of interviews using questionnaires measuring physical activity, unhealthy eating patterns, and sleep quality with the criteria that a doctor diagnosed the respondent as suffering from Type 2 DM and not suffering from other types of Diabetes Mellitus (DM). Data analysis used the odds ratio test, the results showed that physical activity (OR=4.455 and CI=2.250-8.819), unhealthy eating patterns (OR=3.145 and CI=1.616-6.120), sleep quality (OR=5.444 and CI= 2,703 10,966), and dyslipidemia (OR=4,287 and CI=2,121-8,667) are determinants of the risk of Type 2 DM. It is suggested that health workers should improve health services at each Integrated Development Post (known as POSBINDU), an integrated monitoring and early detection activity for NCD risk factors (heart and blood vessel disease, diabetes, acute obstructive pulmonary disease, and cancer) as well as disorders due to accidents and acts of domestic violence which are managed by the community through integrated guidance, meanwhile, provide education on healthy lifestyles to overcome the incidence of DM